USP53 activated by H3K27 acetylation regulates cell viability, apoptosis and metabolism in esophageal carcinoma via the AMPK signaling pathway. (17th December 2021) - Cheng, Wei; Tang, Yong; Tong, Xiaobin; Zhou, Qin; Xie, Jingrong; Wang, Jinlong; Han, Yun; Ta, Na; Ye, Zhou
Abstract: Esophageal carcinoma (ESCA) is a leading cause of cancer death worldwide, despite an overall decline in the incidence of new cases. However, knowledge of gene expression signatures for risk and prognosis stratification of ESCA is inadequate. Thus, identifying novel molecular biomarkers and therapeutic targets for ESCA might improve its prognosis and treatment. The current study investigated the role of ubiquitin-specific peptidase 53 (USP53), a member of the USP family that exhibits deubiquitinating activity, in ESCA and showed that USP53 is downregulated in ESCA tissues, indicating poor prognosis. USP53 suppresses the proliferation and growth of ESCA cells in vitro and in vivo, whereas its knockdown exerts opposite effects. AMP-activated protein kinase inhibitor reverses the effects of USP53 knockdown. USP53 also inhibits glycolysis, oxidative metabolism and mitochondrial dynamics. H3K27 acetylation increases USP53 expression by binding to its promoter region. Our study reveals that USP53 is activated by H3K27 acetylation and suppresses ESCA progression by regulating cell growth and metabolism. USP53 is therefore a promising target for ESCA treatment. Abstract : In this work, we show that the USP53/AMPK axis may play a significant role in esophageal carcinoma cell viability, apoptosis and metabolism. Targeting the axis may prove beneficial in preventing viability, promoting apoptosis and providing a more effective therapeutic strategy for esophageal carcinoma.